Cultural Tourism: Study of Wonorejo Nationalistic Village - Nugroho, Rusdi Hidayat; Prabowo, Budi; Rasyidah, Resa; Nuryananda, Praja Firdaus (Nusantara Science and Technology Proceedings, 2020)
Wonorejo is a rural area located in the Situbondo regency where people come from many religions are living in harmony. The village itself thus was renamed or labeled as “Wonorejo Nationalistic Village” or “Desa Kebangsaan Wonorejo”. As Indonesia is a state that recognizes many cultures, many ethnicities, and many religions, the harmony in Wonorejo could reflect the harmony of Indonesia on a local scale. The label then posited Wonorejo as a tourism destination for its cultural tourism. But in recent years, Wonorejo is found struggling in accelerating its tourism. The advancement of technology and the growth of the tourism industry have held Wonorejo’s socio-economic development from tourism. This study explores the challenges faced by Wonorejo as one of the tourism destinations in Situbondo. The research also examines the effectiveness of asset management in Wonorejo Nationalistic Village. Using the asset-based community development concept and participatory research method, the study dug deep into the problems found in Wonorejo. We found that personal assets and financial assets still become problems in Wonorejo. Furthermore, Wonorejo needs a strong leadership not only from the head of the village but also from the village communities’ vocal persons. They need to line-up the strategies to strengthen the label of “nationalistic village” so that the cultural asset in Wonorejo would not only transform into cultural tourism but also ecotourism.